THE CIRCULATION OF POLITICAL ELITES IN THE DEMOCRATIC CONDITIONS AND ITS PECULIARITIES ON THE POSTCOMMUNIST AREA - Романюк, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The problem of political elites circulation are considered in this article. The author, emphasing of stipulation of this process by the character of the political regime, pays special attention to the peculiarities and development of the mechanism of the political elites circulation in postcommunist conditions.